Identification of a novel aromatic-turmerone analog that activates chaperone-mediated autophagy through the persistent activation of p38 - Motomura, Kensuke; Ueda, Erika; Boateng, Alex; Sugiura, Masaharu; Kadoyama, Keiichi; Hitora-Imamura, Natsuko; Kurauchi, Yuki; Katsuki, Hiroshi; Seki, Takahiro (Frontiers in Cell and Developmental Biology, 2024)
Aromatic (Ar)-turmerone is a bioactive component of turmeric oil obtained from Curcuma longa. We recently identified a novel analog (A2) of ar-turmerone that protects dopaminergic neurons from toxic stimuli by activating nuclear factor erythroid 2-related factor 2 (Nrf2). D-cysteine increases Nrf2, leading to the activation of chaperone-mediated autophagy (CMA), a pathway in the autophagy-lysosome protein degradation system, in primary cultured cerebellar Purkinje cells. In this study, we attempted to identify novel analogs of ar-turmerone that activate Nrf2 more potently and investigated whether these analogs activate CMA. Four novel analogs (A4-A7) from A2 were synthesized. Although all analogs, including A2, increased Nrf2 expression, only A4 activated CMA in SH-SY5Y cells. Additionally, A4-mediated CMA activation was not reversed by Nrf2 inhibition, indicating that A4 activated CMA via mechanisms other than Nrf2 activation. We focused on p38, which participates in CMA activation. Inhibition of p38 significantly prevented A4-mediated activation of CMA. Although all novel analogs significantly increased the phosphorylation of p38 6 h after drug treatment, only A4 significantly increased phosphorylation 24 h after treatment. Finally, we revealed that A4 protected SH-SY5Y cells from the cytotoxicity of rotenone, and that this protection was reversed by inhibiting p38. These findings suggest that the novel ar-turmerone analog, A4, activates CMA and protects SH-SY5Y cells through the persistent activation of p38.